The impact of socio-economic factors on small business success - Saleem, ﻿Muhammad Amjad (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
﻿Small enterprises play a vital role in economic development as they can provide the economy with efficiency, innovation, competition and employment. Entrepreneurs are responsible for the success of their businesses and have to face up with definite challenges in doing so. To know what constitute critical determinants of small business success data were collected from 60 randomly selected respondents in the Dera Ismail Khan district, Khyber Pakhtunkhawa, Pakistan, who were administered with structured questionnaires. Regression analyses of the findings showed the positive and significant impact factors of investment, entrepreneurial experience, business profile and culture with R2=0.638 and F= 11.222. The provision of ample opportunities to develop skills for business enhancement is suggested as the rational way forward.